1991
DOI: 10.1073/pnas.88.15.6472
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 6 enhances a cellular activity that functionally substitutes for E1A protein in transactivation.

Abstract: An interleukin 6 (IL-6)-regulated cellular activity in HepG2 cells is found to functionally substitute for the transcriptional transactivator product of the adenovirus transforming gene E1A in transactivating E1A-dependent and E1A-responsive viral early genes. Mutant viruses deficient in E1A expression replicate in HepG2 cells. Induction with IL-6 leads to significant enhancement of synthesis of viral early E1B and E2ae mRNAs by greater than 30-fold and increases viral replication to the wild-type levels. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 40 publications
(30 reference statements)
1
36
0
Order By: Relevance
“…This result confirms earlier findings of residual expression of adenoviral genes such as E2, E3 and E4, [2][3][4] whose promotors are active at higher MOIs. Not surprisingly, a low level of replication of E1-deleted vectors in target cells under certain circumstances and in certain cell lines has been reported in vitro 28 and in vivo. 4 We were able to confirm adenoviral replication in HepG2 cells and extend this finding to all three other cell lines (A2, HuH7, A549) examined.…”
Section: Discussionmentioning
confidence: 99%
“…This result confirms earlier findings of residual expression of adenoviral genes such as E2, E3 and E4, [2][3][4] whose promotors are active at higher MOIs. Not surprisingly, a low level of replication of E1-deleted vectors in target cells under certain circumstances and in certain cell lines has been reported in vitro 28 and in vivo. 4 We were able to confirm adenoviral replication in HepG2 cells and extend this finding to all three other cell lines (A2, HuH7, A549) examined.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 It was demonstrated earlier that cellular transcription factors can functionally substitute E1A in its transactivator function, which makes the E2 and the E4 promoter potential candidates for interference. [15][16][17] The pIX promoter is orientated rightwards with respect to the viral genome and is located directly adjacent to the E1 insertion site for transgene cassettes. Besides enhancers that act distance and orientation independent, viral sequences contain transcription factor binding sites that represent upstream regulatory elements (UREs).…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon has been reported before with the presence of IL-6 or papillomavirus E6 and E7 allowing replication of E1-deleted viruses. [60][61][62][63][64] In fact, it was demonstrated that factors produced by primary ovarian cancer cells allowed similar replication of an E1-deleted virus and a wild-type adenovirus. 60 While xenografts have traditionally been utilized for investigation of therapeutic efficacy, receptor levels on these cancer cell lines may not correspond well with primary tumors.…”
Section: Discussionmentioning
confidence: 99%